2011
DOI: 10.1007/s00213-011-2472-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modafinil on cognitive functions in first episode psychosis

Abstract: Modafinil selectively enhances working memory in first episode psychosis patients, which could have downstream effects on patients' social and occupational functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 50 publications
3
43
0
2
Order By: Relevance
“…Phase 1 studies have shown improvements in attentional set-shifting in schizophrenia following sertindole (Gallhofer et al 2007) and modafinil in patients with chronic schizophrenia (Turner et al 2004), but not in first-episode psychosis (Scoriels et al 2012). Although both sertindole and modafinil have been shown to improve ASST in the scPCP model providing back-translation of clinical findings, these findings have not been confirmed in larger, late-stage clinical trials, and neither treatment has been approved for the treatment of cognitive impairment in schizophrenia.…”
Section: Attentional Set-shifting Taskmentioning
confidence: 96%
“…Phase 1 studies have shown improvements in attentional set-shifting in schizophrenia following sertindole (Gallhofer et al 2007) and modafinil in patients with chronic schizophrenia (Turner et al 2004), but not in first-episode psychosis (Scoriels et al 2012). Although both sertindole and modafinil have been shown to improve ASST in the scPCP model providing back-translation of clinical findings, these findings have not been confirmed in larger, late-stage clinical trials, and neither treatment has been approved for the treatment of cognitive impairment in schizophrenia.…”
Section: Attentional Set-shifting Taskmentioning
confidence: 96%
“…Results indicate that modafinil enhances verbal and spatial working memory and improves accuracy in tasks measuring impulsivity (Scoriels et al, 2012). Modafinil had, however, no effect on sustained attention, attentional set-shifting, learning or fluency.…”
Section: Schizophrenia and Psychosismentioning
confidence: 97%
“…Nine studies fulfilling these criteria were identified by April 2012 (Table 1). There were five single dose administration crossover designed studies (Farrow et al, 2006;Minzenberg et al, 2008;Scoriels et al, 2012;Spence et al, 2005;Turner et al, 2004b) and four chronic dose administration (8 weeks) parallel designed studies (Arbabi et al, 2012;Freudenreich et al, 2009;Pierre et al, 2007;Sevy et al, 2005). In total, these studies involved 228 patients, with various diagnoses (first episode psychosis, schizophrenia, schizoaffective disorders), different age ranges (range: 25e49.8, average: 38.3 years of age), sex-ratios (range: 0.4e9.5, average: 3.3), IQ scores (these were not systematically collected), duration of illness (range: 1.4e19.5, average: 12.2 years) and anti-psychotic prescription (six studies included patients on several antipsychotics and two studies examined the specific interaction between modafinil and clozapine and risperidone, respectively).…”
Section: Individual Studies Included In the Reviewmentioning
confidence: 99%
“…While it is difficult to draw general conclusions on the basis of the limited available evidence, some cognitiveenhancing drugs have shown promising results for CIAS (e.g. minocycline, modafinil, galantamine), where they generally tended to improve isolated cognitive domains without a clear effect on overall cognition: minocycline for example improved working memory, cognitive flexibility and planning (Levkovitz et al, 2010), galantamine improved verbal memory and processing speed (Buchanan et al, 2008), while modafinil improved attentional set shifting in chronic patients with schizophrenia (Turner et al, 2004) and working memory in patients with first-episode psychosis (Scoriels et al, 2012). The nicotinic alpha-7 agonist EVP-6124 has however demonstrated a significant effect on global cognitive function compared to placebo in patients with schizophrenia in a multi-site phase II trial in 319 patients with schizophrenia (News release of EnVivo pharmaceuticals at http://www.envivopharma.com/news-item.php?id=35) and it is currently tested in larger phase III trials for CIAS in patients with schizophrenia (Clinical trials gov.…”
Section: Cognitive-enhancing Drugsmentioning
confidence: 98%